Sweatch / Nor Safiza Zolkipli … [et al.] - Zolkipli, Nor Safiza; Jasni, Aida Wanie; Mohd Rani, Nabilah Shahirah; Yusmahaidi, Nur Syafiqah; Amerudin, Nur Qistina; Shafiai, Syahiru (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Smartwatch technology has advanced significantly over time and they have also grown in popularity. They are frequently outfitted with sophisticated fitness trackers capable of analysing every movement and some of the apps are actually useful. A smartwatch is a portable device that is worn on the wrist. They like smartphones, have touchscreens, apps and frequently record our heart rate and other vital signs. When compared to other watches, the most popular smartwatches are extremely expensive but it is a poor investment when compared to a smartphone. The most of smartwatches require charging every one to two days. Given the functionality, this is understandable, but it is something to consider if we intend to replace a traditional watch. Furthermore, a smartwatch for outdoor activities is frequently used to supplement other, bulkier devices in an adventurer's tool kit. People are most concerned about the battery life of smartwatches. Instead, sweat technology could supplement standard charging, requiring us to charge our smartwatch far less frequently than we do now. Sweat is an especially promising energy source because it contains lactate, a natural by-product of anaerobic respiration (the method our bodies use to get energy quickly when we exert ourselves), which can be broken down by an enzyme to produce energy. Also, most smartwatches are marketed as waterproof, but this usually refers to water resistance rather than the ability to submerge them for a longer duration. Many smartwatches, for example, are more vulnerable to saltwater damage than traditional watches, which are frequently designed for swimming in the sea. Sweatch, on the other hand, has been proven to be water resistant because it generates energy through sweat.